Work Experiences of Successful Men with Same Sex Attraction - de Guzman, Jemos S..; Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations, 2021)
This exploratory qualitative study examined the attitude of the workplace towards Filipino homosexual men and how such affected their behavior at work. Fifteen homosexual men occupying supervisorial to top management positions were interviewed. To validate their responses, two HR practitioners were interviewed while five key informants were tapped for a focus group discussion. Results showed that there were distinct and defined unwritten rules of acceptable behavior of Filipino homosexual men in the workplace. Disclosed homosexual men were confined to several negative stereotypes. Non-disclosed ones, on the other hand, usually became the subject of talk and gossip. As a response, Filipino homosexual men had to either conform to the rules or battle out the negative perceptions of them such as taking advantage of their positive traits such as being a hard worker, being flexible and reliable, and their going for the extra mile in order to gain respect and achieve success in their careers.